A Comparative Study on the Impact of Fasting on Blood Glucose and Blood Pressure Among Diabetic and Non-Diabetic Individuals During Ramadan, Kurdistan Region, Iraq - Salih, Banaz Abed; Ali, Himan Ibrahim; Ramadhan, Shireen Hosny (Technium BioChemMed, 2024)
Objective: The primary aim of this research was to evaluate the differential effects of regular and fasting dietary patterns on blood glucose levels and blood pressure among diabetic patients and non-diabetic control group. A comprehensive analysis was conducted to compare physiological responses on fasting versus non-fasting days during the holy Ramadan month. Methods: This observational study involved 92 participants, with a subset of 38 diabetic patients and 54 non-diabetic control group, aged 19-76 years, who were observed on regular and fasting days. Participants were monitored for pre-prandial, postprandial, evening blood sugar, and fasting blood glucose levels, as well as blood pressure. Statistical analysis was performed using paired sample t-tests to compare mean ± SD between regular and fasting days of both groups. The study cohort consisted of male and female adults diagnosed with type 1 or type 2 diabetes. Exclusion criteria included individuals under 18 years, pregnant women, and patients unable to fast during the study period. Results: Statistical analysis revealed significant differences in fasting blood glucose levels during Ramadan compared to non-fasting days. In the diabetic group, significant changes were observed in fasting blood glucose levels during Ramadan compared to after Ramadan ( postprandial blood sugar p=0.04, evening blood sugar p=0.019). In contrast, the non-diabetic group also showed significant changes in blood glucose levels during Ramadan compared to after Ramadan (postprandial blood sugar p=0.001, evening blood sugar p=0.020). Blood pressure showed no significant differences between these periods, suggesting that fasting does not alter blood pressure significantly in diabetic individuals. Additionally, a two-way ANOVA demonstrated significant dietary influences on post-Iftar glucose levels in non-diabetics (p<0.001), but not in diabetics, suggesting differential metabolic responses to dietary intake during Ramadan. These findings emphasize the critical need for personalized dietary management and continuous monitoring to optimize diabetic care during fasting. Conclusion: Fasting significantly influences blood glucose levels in diabeticand non-diabetic individuals but does not affect blood pressure. This study underscores the necessity for personalized medical guidance and balanced meal planning to minimize complications and enhance diabetes management during fasting. Further research is warranted to explore the long-term effects of different fasting practices on diabetic health outcomes.